Modeling Facebook users' behavior towards the use of pages related to healthy diet and sport activities - Nikolaos Misirlis; Marjon Elshof; Maro Vlachopoulou (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: In this article we aim to model social media users' behavior in relation with the use of specified Facebook pages and groups, related to eHealth, specifically to healthy diet and sport activities. The study represents to the best of our knowledge the first region-focused on a specific geographical area research. Methods: The users' personality is measured through the well-known Big Five model and the behavior is predicted with the Theory of Planned Behavior (TPB). Structural Equation Modeling is used in order to statistically control the associations among the diverse observed and latent variables. Results: The results suggest an extended theory of planned behavior in combination with personality traits, on eHealth field. Openness and Extraversion do not seem to have positive effect on Attitude. Users' attitude can be affected positively from Agreeableness and Subjective Norms, guiding to finally positive affection of users' actual behavior. Agreeableness cannot influence behavior, directly, nor through SN, since the hypothesis path A-SN is not verified, but it can through Attitude. Neuroticism was negatively correlated to PBC but this hypothesis was not, also, confirmed in the proposed model. Implications: While literature confirms all of our hypotheses, in our study only 8 in 12 are finally confirmed. The difference between the present model and literature findings can be located on the different cultural dimensions among the different studies. The present survey is focused on the Greek region with all the participants to be Greeks. This location-based limitation could be surpassed by conducting the same research on different geographical regions and then confront the outcomes.
Keywords: C31; O35; L86; 330; Big Five Personality Model; Personality traits; Facebook; Theory of Planned Behavior